Study on Correlation between IL-33 serum level, IL-33 Gene Single Nucleotide Polymorphism and Rheumatoid Arthritis Susceptibility - Hind Fouaad alhammami1 , Mahdi H. AL-Ammar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: To discuss the association between single nucleotide polymorphism (SNP) of rs1929992 in IL- 33gene and IL-33 serum level in rheumatoid arthritis (RA) susceptibility among Iraq population. Methods: A total of 50 samples were collected from 35 RA patients from November 2018 untill end of January 2019 together with 15 healthy physical examines in the same period were chosen as the subjects. The serum IL-33 levels measured by commercial ELISA kits . Erythrocyte sedimentation rate ,white blood cell were measured by standard laboratory techniques The RFLP-PCR reaction technique was used to detect the genotype distributions for rs1929992 in IL-33gene was carried out by using restriction enzyme. The frequency of each allele and genotypes distribution was calculated so as to evaluate the association between genotype distribution and RA susceptibility. Results: Serum IL-33concentration was significantly higher in patients with RA than in control groups. The homozygous genotype AA recorded higher frequency in RA patients (42.9%) than controls (6.7%) with a significant difference (P-value 0.001). Homozygote genotype GG frequency (45.7%) was a significant in patients compared to controls subject (33.3%) with a significant difference (P-value 0.016), and the genotype heterozygous GA frequency (11.4%) were non-significant in patients compared to controls (60.6%). The allele frequency for allele G was (51.4%)in patients compared with controls ( 63.3%) with a significant difference (P-value 0.022)while for the allele A was (48.6%) in patients compared with controls( 36.7% )with a significant difference (P- value 0.001). Conclusions: significant correlation between RA patients susceptibility and genotype AA and alleles at rs1929992in IL-33 gene is observed. From this study showed that the IL-33 levels were influenced by genetic variation at SNPs rs5743708and rs1929992, respectively.